Analisis Preferensi Mahasiswa Fakultas Ekonomi dan Bisnis Terhadap Media Belanja Digital - Andrieka Natalia Christianty; Rinesia Sulistya Sirait; Yemima Agustin Kaban; Timothy (Jurnal Semesta Ilmu Manajemen dan Ekonomi, 2025)
The rapid development of digital technology has transformed various aspects of daily life, particularly among university students. This study aims to analyze the preferences of students from the Faculty of Economics and Business regarding the use of e-commerce as a digital shopping medium, focusing on the platforms used, types of products purchased, preferred payment methods, and ease of use. This research employs a descriptive quantitative approach and survey method involving 68 student respondents. Data were analyzed using descriptive statistics and the chi-square test to examine the relationship between e-commerce platforms and both product categories and payment methods, supported by qualitative analysis from open-ended questionnaires. The results show that Shopee is the most dominant platform, with a usage rate of 72.1%, followed by TikTok Shop. The most frequently purchased products are cosmetics and fashion, with most of these purchases made via Shopee. Bank transfer was the most preferred payment method (61.8%), although COD is still used by some respondents. The chi-square test revealed a statistically significant relationship between the e-commerce platform and the type of product purchased (p < 0.05), but no significant relationship was found between platform choice and payment method (p > 0.05). This study concludes that students' preferences are influenced by ease of use, dominant product categories, and flexible payment options. These findings are expected to inform e-commerce platform developers in formulating marketing strategies that align with student consumer behavior.